Los hechos notorios en materia civil en el Derecho Comparado Latinoamericano. - Pintag Tixi, Joel Stalyn (2023)
Notorious fact is a figure that is part of procedural law characterized by being in the public domain and, therefore, exempting itself from evidence, taking them as genuine. Although the law allows them to be invoked in judicial proceedings, it does not contain a legal definition; as such, this research aims to analyze through a doctrinal, legal, and comparative study the characteristics and criteria for determining the notorious facts to establish whether the current procedural legal norm that regulates them is sufficient. The researcher applied historical-logical, legal-doctrinal, analytical, descriptive, and legal comparison methods to accomplish the research objective. The research was qualitative and was documentary-bibliographic, analytical, and descriptive. The results show that the General Organic Code of Proceedings needs to contain an adequate legal definition of notorious facts, which does not facilitate their determination and hinders the judge's work on an abstract and relative figure concerning time and space.